The study of biological active compounds of lipophilic fraction of Schisandra chinensis (Turcz.) Baill seeds - Melnyk , Inna; Kovalska , Nadiya; Karpiuk , Uliana; Skripchenko , Nadiya (The Ukrainian Scientific Medical Youth Journal, 2022)
Schisandra chinensis (Turcz.) Baill - Chinese magnolia - a well-known fruit plant in traditional Chinese and Korean medicine. The fruits and seeds of S. chinensis are rich in biologically active substances. According to the literature (Irfan M. etc, 2020; Liu G-Z. etc, 2020; Sun W. etc, 2021; Zhao T. etc., 2021; Bodrevich B.B. etc, 2017) the following therapeutic effects of S. chinensis fruits and seeds can be called: immunomodulatory, tonic, adaptogenic, anti-inflammatory, hepatoprotective, nephroprotective, tonic. The study of the S. chinensis raw materials continues in the future, to reveal a wider range of therapeutic actions. The study of S. chinensis seeds is quite relevant to expand the range of standardized medicinal raw materials, which is not included in the monographs of the State Pharmacopoeia of Ukraine. The main purpose of this study is to obtain the lipophilic fraction of S. chinensis seeds and to study the composition of different groups of lipophilic substances in the resulting fraction. The main method of obtaining the lipophilic fraction of S. chinensis seeds is a comprehensive extraction in the Soxhlet apparatus. The chemical reaction was used to determine the presence of tocopherols. The presence of the main groups of biologically active substances in the lipophilic fraction of S. chinensis seeds was established by the method of two-dimensional thin-layer chromatography. The study of fatty acid composition was performed by gas chromatography/mass spectrometry (Su L. etc, 2020). The yield of lipophilic fraction of S. chinensis seeds was 35.79±0.7%. The obtained lipophilic fraction of S. chinensis seeds is an oily liquid of deep yellow color with a characteristic specific odor. The presence of tocopherols was established. Thin layer chromatography in the solvent system: I direction - hexane-acetone (8: 2), II direction - hexane-acetone (8: 4), development reagent - Stahl reagent, identified at least 14 compounds of terpene nature. As a result of studies of fatty acids by gas chromatography/mass spectrometry, the quantitative content of 6 fatty acids was identified and established: palmitic, linoleic, oleic, stearic, gondoic and nonadecanoic. The quantitative content of unsaturated fatty acids significantly exceeded the quantitative content of saturated fatty acids. The results of the study give grounds to draw the following conclusions: the studies confirm the rich composition of the lipophilic fraction of S. chinensis seeds: tocopherols, 14 terpenes, 6 fatty acids, of which saturated fatty acids (palmitic, stearic, nonadecanoic) and unsaturated fatty acids , oleic and gondoin); The results of the study suggest the anti-inflammatory, antioxidant, regenerating effect of the lipophilic fraction of S. chinensis seeds.